Transformative Sustainable Education Approach as Environmental Literacy Transformation: Case Study of Ecosystem Material in Elementary Schools - Ekantini*, Anita; Wijayanti, Inggit Dyaning; Andania, Ruqoyyah Amilia (Jurnal Pendidikan Sains Indonesia, 2024)
The adiwiyata program has been implemented in several elementary schools in Indonesia, but its implementation has yet to be integrated into learning. The objectives of this research are: 1) To find out the implementation of the Transformative Sustainable Education (TSE) approach in Natural and Social Science (NSS) learning; 2) To find out whether the implementation of the TSE approach is effective in improving students' environmental literacy. This TSE approach is implemented in natural and social sciences learning. This research used an experimental method with pretest-posttest control group design. The population of this study were 5th grade students of MIN 2 Bantul which consisted of class A and class B. The sample was selected by cluster random sampling and the students were selected. The sample was selected by cluster random sampling and class A of 29 was selected as the experimental class and class B of 28 as the control class. The instruments used in this study include observation sheets of learning implementation with the TSE approach and environmental literacy observation sheets. The results showed that: 1) The TSE approach was implemented with a percentage of 95% in the very good category; 2) The TSE approach was effective in improving environmental literacy in the medium category.